Executives' “off-the-job” behavior, corporate culture, and financial reporting risk - Davidson, Robert; Dey, Aiyesha; Smith, Abbie (Journal of Financial Economics, 2015)
We examine how executives' behavior outside the workplace, as measured by their ownership of luxury goods (low “frugality”) and prior legal infractions, is related to financial reporting risk. We predict and find that chief executive officers (CEOs) and chief financial officers (CFOs) with a legal record are more likely to perpetrate fraud. In contrast, we do not find a relation between executives' frugality and the propensity to perpetrate fraud. However, as predicted, we find that unfrugal CEOs oversee a relatively loose control environment characterized by relatively high and increasing probabilities of other insiders perpetrating fraud and unintentional material reporting errors during their tenure. Further, cultural changes associated with an increase in fraud risk are more likely during unfrugal (vs. frugal) CEOs' reigns, including the appointment of an unfrugal CFO, an increase in executives' equity-based incentives to misreport, and a decline in measures of board monitoring intensity.